Penerapan Internet, Intranet, Dan Ekstranet Di Rumah Sakit (Studi Literature) - Dinda Bestari; Vip Paramarta; Nuryanti Nuryanti; Rizki Tomi Resna Suhendar (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Healthcare professionals play a crucial role in enhancing the quality of healthcare services provided to the community. It is essential for healthcare workers to be familiar with the available internet, intranet, and extranet access within hospitals. The significance of such access for healthcare professionals lies in their ability to exercise caution and maintain the confidentiality of patient information in the digital era. The purpose of having this access for healthcare workers is to understand the utilization and differentiate between applications available in hospitals that fall under internet, intranet, and extranet access. Additionally, it allows them to delve deeper into subjects in theory or research and assist readers in better understanding them, along with their implications. This article discusses the definition, differences, and examples of applications available in hospitals with internet, intranet, and extranet access.